2019
DOI: 10.1126/science.aax0164
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization of stem cells into embryos: A window on early mammalian development

Abstract: 2 Embryonic development is orchestrated by robust and complex regulatory mechanisms acting at different scales of organization. In vivo studies are particularly challenging for mammals after implantation, due to the small size and inaccessibility of the embryo. The generation of stem cell models of the embryo represents a powerful system to dissect this complexity. Control of geometry, modulation of the physical environment, and priming with chemical signals reveals the intrinsic capacity of embryonic stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
120
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(132 citation statements)
references
References 67 publications
1
120
0
3
Order By: Relevance
“…Highmagnification spinning disc confocal imaging showed that the hESCs collectively migrated to these nodes and further revealed that many ingressed basally upon reaching the node to ultimately assemble into a second cellular layer that expressed the mesoderm marker T(brachyury) ( Figure 1C). This cellular behavior is highly reminiscent of gastrulation, wherein cells of the developing epiblast collectively migrate towards the midline and ingress to form a secondary transient structure called the primitive streak, which gives rise to the mesoderm and endoderm germ layers (Shahbazi et al, 2019;Shahbazi and Zernicka-Goetz, 2018;Simunovic and Brivanlou, 2017;Voiculescu et al, 2014;Williams and Solnica-Krezel, 2017). Analogous to the embryonic primitive streak that expands as gastrulation progresses, these "gastrulation-like" nodes in the hESC colonies similarly continued to expand between 24 and 48 hours post-BMP4-stimulation ( Figure 1E).…”
Section: Compliant Substrates Promote Hesc Self-organization Into "Gamentioning
confidence: 95%
“…Highmagnification spinning disc confocal imaging showed that the hESCs collectively migrated to these nodes and further revealed that many ingressed basally upon reaching the node to ultimately assemble into a second cellular layer that expressed the mesoderm marker T(brachyury) ( Figure 1C). This cellular behavior is highly reminiscent of gastrulation, wherein cells of the developing epiblast collectively migrate towards the midline and ingress to form a secondary transient structure called the primitive streak, which gives rise to the mesoderm and endoderm germ layers (Shahbazi et al, 2019;Shahbazi and Zernicka-Goetz, 2018;Simunovic and Brivanlou, 2017;Voiculescu et al, 2014;Williams and Solnica-Krezel, 2017). Analogous to the embryonic primitive streak that expands as gastrulation progresses, these "gastrulation-like" nodes in the hESC colonies similarly continued to expand between 24 and 48 hours post-BMP4-stimulation ( Figure 1E).…”
Section: Compliant Substrates Promote Hesc Self-organization Into "Gamentioning
confidence: 95%
“…The advent of in vitro models of mammalian development 8,9 provides several advantages: firstly, unlike embryos, such systems are amenable to systematic perturbations. The system size and its composition can be conveniently modulated by changing the type and the initial number of cells seeded.…”
Section: Introductionmentioning
confidence: 99%
“…Development is one example of multiscale emergent behavior in which molecular 2 interactions between cells allow self-organization into multicellular patterns. One of the 3 most remarkable features of all types of development is how robust it is in the face of 4 genetic and environmental perturbations, suggesting that backup systems are in 5 place [27]. While molecular genetics has identified mutations that impede multicellular 6 development, even single mutations create downstream effects that influence multiple 7 aspects of cell behavior and physiology.…”
mentioning
confidence: 99%
“…These behaviors include reduced movement inside the aggregate and 24 a bias in directed movement toward the aggregation centers, likely via chemotaxis [34]. 25 This methodology provides an unprecedented window into developmental behavior that 26 is presently difficult to realize in larger organisms with thicker tissues or longer cell 27 migration routes, such as the vertebrate neural crest or in disease states such as tumor 28 metastases. 29 In this work we examined reciprocal interactions between WT cells mixed with 30 non-developing mutants.…”
mentioning
confidence: 99%